Using of GGE biplot in determination of genetic structure and heterotic groups in wheat (Triticum aestivum L.) - Shamsabadi, Ensieh Es'haghi; Sabouri, Hossein; Soughi, Habibollah; Sajadi, Seyed Javad; Dadras, Ahmad Reza (Acta Biologica Szegediensis, 2021)
The present study was undertaken to analyze diallel data using GGE biplot model to gather information about genetic interrelationships among parents and identiﬁcation of heterotic combinations for yield and yield components in bread wheat varieties. For this purpose, 8 bread wheat genotypes tested across in half-diallel crosses design, GGE biplot technique was used. Parents included the genotypes of Kouhdasht, Karim, Ehsan, Mehregan, N-92-9, Line 17, N80-19 and Atrak. The hybrids obtained from the one-way cross (28 hybrids) in agricultural years of 2016-17 were evaluated as randomized complete block design in two replications on the research farm of Gonbad Kavous University. The evaluated traits included the grain yield, weight of spike grains, number of grains in spike and number of spikes. Additive main eﬀects and genotype × environment interaction (GGE) were employed in the evaluation of genotypes; analyses showed signiﬁcant (P< 0.01) G × E, (genotype × environment interaction) with respect to plant seed yield. GGE biplot analysis showed that Karim was as the best general combiners for grain yield, number grain per spike and grain weight per spike, whereas Ehsan had the highest GCA eﬀects for number of spikes. Ehsan and Karim had higher speciﬁc combining ability than other genotypes. The studied genotypes for this trait were divided into two heterotic groups where the ﬁrst group included the genotypes of Kouhdasht, N-92-9, N80-19 and Atrak and the second group contained the genotypes of Line 17, Mehregan and Karim. Mehregan line had a weak combining ability with all testers and N-92-9 had also more power than others. Based on the biplot, the Karim genotype with high general adaptation was introduced as the ideal genotype in terms of grain yield, spike number, grain number per spike and grain weight, so the Karim genotype can be adapted to obtain high yield hybrids.